The Influence of The Value Clarification Technique (VCT) Learning Model and The National Insight on The Character of Elementary School Students - Yusrizal, Yusrizal; Hariati, Emy (Universitas Negeri Medan, 2022)
This research is motivated by the phenomenon of character and morals of elementary school students who are increasingly being degraded after the COVID-19 pandemic. Distance learning is the main trigger that causes students to become more passive in interacting with the surrounding environment. The main objective of this research is to find a new paradigm in post-COVID-19 learning that is able to improve the character of elementary school students after distance learning. The specific objectives of this study are 1) to analyze the effect of the Value Clarification Technique (VCT) learning model on the character of elementary school students; 2) Analyzing the differences in the character of students based on the level of national insight; and 3) Analyzing the interaction between the VCT learning model and national insight in influencing students' character. This research was conducted at SDN PAB 16 Klambir V, Hamparan Perak District. The research instrument uses a national insight test and a student character score questionnaire that has been validated by experts. The data analysis technique used Two Way Anova. The results showed that 1) the use of the Value Clarification Technique (VCT) learning model had a positive effect on increasing student character values after the COVID-19 pandemic; 2) The character of students with high national insight is better than the character of students with low national insight; and 3) There is an interaction between the Value Clarification Technique (VCT) learning model and national insight in influencing the character of elementary school students after the COVID-19 pandemic.